EFFECTS OF THE NANO PARTICLE CONCENTRATION AND TYPE ON NATURAL CONVECTION HEAT TRANSFER FROM HORIZONTAL CONCENTRIC CYLINDER SYSTEMS COOLING IN THE AMBIENT AIR - Demir, Hakan; Atayilmaz, S. Ozgur; Agra, Ozden; Teke, Ismail (AMER SOC MECHANICAL ENGINEERS, 2013)
Natural convection heat transfer from horizontal concentric cylinders is studied experimentally and numerically. Concentric cylinder was formed with two cylinders made of copper, and the annulus was filled with water. Concentric cylinder system was located in the ambient air and the inner horizontal cylinder was kept at a constant temperature. Experimental study was carried out in a conditioned room which can be maintained at a stable required value and inside a sufficiently designed test cabin. The inner copper cylinder surface temperatures varied between 30 C-50 degrees C and ambient temperature was 20 degrees C. On the basis of the experimental data average Nusselt numbers for the air side of the concentric cylinders were calculated and compared with numerical results. The effective thermal conductivity of the annulus was calculated by using the experimental data and numerical solution results and compared. Besides, heat transfer enhancement in horizontal annuli has been investigated for different nano particle concentrations. Water based nano fluid containing Al2O3 nano particles have been used. Isotherms and streamlines are presented in the annulus and the air side. Heat transfer rates under steady state conditions for different nano particle concentrations were compared and heat transfer enhancement was determined.
Keywords: TURBULENT FREE-CONVECTION; TRANSFER ENHANCEMENT; CORRELATING EQUATIONS; ELLIPTIC CYLINDERS; LAMINAR; ANNULUS; WATER; FLOW; SIMULATION; Engineering